The rise of corporate religious liberty - Schwartzman, Micah Jacob 1976-; Flanders, Chad; Robinson, Zoë (Oxford Oxford University Press, 2016)
'The Rise of Corporate Religious Liberty' explores this 'corporate' turn in law and religion. Drawing on a broad range of perspectives, this book examines the idea of 'freedom of the church', the rights of for-profit corporations, and the implications of the Supreme Court's landmark decision in Burwell v. Hobby Lobby Stores, Inc.
Keywords: Hobby Lobby (Firm); Freedom Of Religion -- United States; Corporation law -- United States; Corporations -- United States -- Religious aspects; Corporations, Religious -- Law and legislation -- United States; Religious Pluralism -- United States; Freedom Of Religion -- United States; Corporation law -- United States; Corporations -- Religious aspects -- United States; Corporations, Religious -- Law and legislation -- United States; Religious Pluralism -- United States; Hobby Lobby (Firm); Freedom of religion ; United States; Corporation law ; United States; Corporations ; United States ; Religious aspects; Corporations, Religious ; Law and legislation ; United States; Religious pluralism ; United States; Aufsatzsammlung